Indole-3-Carbinol Enhances Alternative Activation of Macrophages via AHR Pathway and Glucose Transporter Regulation - Delara Omrani; Saeed Mohammadi; Moein Malekzadeh; Mohsen Saeidi; Fakhri Sadat Seyedhosseini; Ahmed Al-Harrasi; Yaghoub Yazdani (Immuno, 2025)
Disruption in macrophage polarization is linked to inflammatory diseases and metabolic disorders. Our study aimed to investigate how AHR activation by I3C and TCDD could impact glucose transporters and macrophage phenotypes and functions in human macrophages. Human monocyte-derived macrophages (hMDMs) and THP-1 cell-derived macrophage-like cells were treated for 24 h with 100 ng/mL LPS, 100 nM TCDD, and 10 ng/µL I3C. CYP1A1 and CYP1B1 expression was significantly increased in the I3C and TCDD treatments, with CYP1B1 showing a higher fold change in I3C compared to TCDD. The AHRR expression was the highest in the TCDD group. For macrophage polarization, I3C significantly elevated CD163 expression while reducing CD16 and CD86, indicative of M2-like polarization. Additionally, I3C promoted ARG1 expression and reduced NOS2 levels, while TCDD increased NOS2. A cytokine analysis revealed I3C-induced upregulation of IL-10 and TGF-β, while TCDD significantly elevated TNF-α and IL-12. I3C upregulated glucose transporter genes (GLUT1, GLUT3, GLUT6), in contrast to the downregulation observed in TCDD-treated cells. Our findings demonstrated that I3C distinctly modulates AHR activation genes, macrophage polarization, cytokine expression, and glucose transporter levels in THP-1 cells compared to the TCDD and LPS treatments. Our findings suggest that I3C favors an anti-inflammatory M2-like macrophage polarization coupled with enhanced metabolic activity.